Advances in Food Process Engineering Research and Applications - Yanniotis, Stavros; Taoukis, Petros; Stoforos, Nikolaos G.; Karathanos, Vaios T. (Food Engineering Series, 2013)
The International Congress on Engineering and Food (ICEF) has been established as the major international event in the field of Food Engineering. The 11th International Congress on Engineering and Food (ICEF11) took place in Athens, May 22-26, 2011 (www.icef11.org). Papers presented in ICEF11 included topics in Food Materials Science, Engineering Properties of Foods, Advances in Food Process Technology, Novel Food Processes, Food Product Engineering & Functional Foods, Food Waste Engineering, Hygienic Design and Operation of Food Plants, Modeling & Control of Food Processes, Food Process Design & Economics, Modeling Food Safety & Quality, and Innovation Management. This book is based on invited contributions to the Congress. Stavros Yanniotis, Professor of Food Engineering, Department of Food Science and Technology, Agricultural University of Athens Petros S. Taoukis, Professor, Laboratory of Food Chemistry and Technology, School of Chemical Engineering, National Technical University of Athens Nikolaos G. Stoforos, Associate Professor of Food Preservation, Department of Food Science and Technology, Agricultural University of Athens Vaios T. Karathanos, Professor of Food Engineering and Physical Chemistry, Department of Nutrition, Harokopion University of Athens.